Promoting commercial forestry in Uganda: The experience of the tree biotechnology programme - Linda Calabrese (Overseas Development Institute (ODI), 2021)
Forests (natural and planted) are a vital resource in East Africa, providing food, fuel and timber for local communities, maintaining the soil and water balance, and absorbing carbon dioxide. Due to increased population pressure and rapidly growing demand for charcoal, East African forests have been shrinking. Towards the end of the 1990s, the Gatsby Charitable Foundation began funding the Tree Biotechnology Programme, a clonal forestry programme aimed at increasing the production of wood for domestic consumption. By focusing on improving tree growers' access to quality planting materials, the programme had a threefold objective: private sector and small grower development, poverty alleviation, and the reduction of negative environmental impact from forestry (contributing to environmental protection). This report analyses and explores the experience of this programme. Its success in Uganda is due to a wide range of factors, both internal and external to the programme. In Uganda, the programme's broad sector view allowed it to thrive, and take advantage of favourable external conditions. This is one reason why Gatsby Africa has since taken a more holistic systems approach to sector transformation. Moving to a direct implementer model, with explicit transformation objectives, has meant that Gatsby Africa has a better picture of what is happening in its programmes, can adapt sooner when challenges arise and can anticipate opportunities for future growth.
Keywords: 330; Uganda; Bio-diversity; Environment; Land